Risk Factors for Diabetes Mellitus Occurrence in the Elderly at the Griya Antapani Public Health Center - Ade Saputra Nasution1, Fitriani Pramita Gurning2, Muchti Yuda Pratama3, Fauzan4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Diabetes Mellitus is a health disorder that is caused by an increase in insulin levels. Diabetes Mellitus, including disease, is also a risk factor for heart and blood vessel disease. Risk factors for Diabetes Mellitus itself from Abdominal/Central Obesity, Hypertension, Dyslipidemia, and smoking. This study aims to see whether there are factors associated with the place of Diabetes Mellitus in the work area of the Griya Antapani Community Health Center. The research method used is Analytical Epidemiology with a Cross-Sectional approach, Sampling many as 84 respondents. The results of study showed that there was a relationship between Abdominal/Central Obesity, Hypertension, dyslipidemia and smoking the relationship between the incidence of Diabetes Mellitus in the Working Area of the Griya Antapani Public Health Center in Bandung. Based on the results of this study, it is expected that the community will find an unhealthy lifestyle to be healthy.